PENGARUH PERLAKUAN BIOFILTRASI EKOSISTEM BUATAN TERHADAP PENURUNAN COD, NITRAT, DAN pH AIR LIMBAH PENCUCIAN RUMPUT LAUT - Anggreni, W. Gina; Budiarsa Suyasa, I Wayan; Dwijani S., Wahyu (Jurnal Kimia (Journal of Chemistry); Vol. 8, No. 1 Januari 2014DO - 10.24843/JCHEM.2014.v08.i01.p16, 2014)
Research on seaweed effluent treatment through biofiltration of artificial ecosystem was carried out to determine the effectiveness, capacity, and the minimum duration of biofiltration process to reduce COD, nitrate and pH in water to meet the quality standard. The result shows that effectiveness of treatment system without added microorganisms are 79.22% for COD, 38.77% for nitrate, and 35.64% for pH; whereas, by adding microorganisms are 83.93% for COD, 55.54% for nitrate, and 36.43% for pH. Capacity of the treatment system without added microorganisms are 12.0653 mg/L/m 3 hr for COD, 0,0089 mg/L/m 3 hr for nitrate, and 0,1444 hr -1 for pH; while, by adding microorganisms are 12,7819 mg/L/m 3 hr for COD, 0,0129 mg/L/m 3 hr for nitrate, and 0,1413 hr -1 for pH. Requisite minimum time in treatment system to meet the quality standard without added microorganisms are 48 hours for COD, 8 hours for nitrate, and 8 hours for pH; whereas, by adding microorganisms are 40 hours for COD, 8 hours for nitrate, and 8 hours for pH.
Keywords: Seaweed washing effluent, Biofiltration, COD, Nitrate, pH